Accurate simulation of delamination under mixed-mode loading using a cohesive model with a mode-dependent penalty stiffness. (15th January 2018) - Turon, A.; González, E.V.; Sarrado, C.; Guillamet, G.; Maimí, P.
Abstract: The cohesive zone model approach in conjunction with a damage formulation, has been used by many authors to simulate delamination using finite element codes. However, some models available in the literature have not been validated correctly under mixed-mode loading conditions. An incorrect selection of the parameters of the model can result in inaccurate simulation predictions. In this work, the cohesive formulation previously developed by the authors has been updated with a mode-dependent penalty stiffness to ensure accurate and reliable simulation results. Different loading scenarios are simulated to validate the accuracy of the new formulation.